Placement matching of alcohol-dependent patients based on a standardized intake assessment: rationale and design of a randomized controlled trial - Buchholz, Angela (BioMed Central, 2014)
BACKGROUND: Despite considerable research on substance-abuse placement matching, evidence is still inconclusive. The aims of this exploratory trial are to evaluate (a) the effects of following matching guidelines on health-care costs and heavy drinking, and (b) factors affecting the implementation of matching guidelines in the treatment of alcohol-dependent patients. METHODS: A total of 286 alcohol-dependent patients entering one of four participating detoxification units and having no arrangements for further treatment will be recruited. During the first week of treatment, all patients will be administered Measurements in the Addictions for Triage and Evaluation (MATE), European Quality of Life-Five Dimensions health status questionnaire (EQ-5D), and the Client Socio-Demographic and Service Receipt Inventory—European Version (CSSRI-EU). Patients who are randomly allocated to the intervention group will receive feedback regarding their assessment results, including clear recommendations for subsequent treatment. Patients of the control group will receive treatment as usual and, if requested, global feedback regarding their assessment results, but no recommendations for subsequent treatment. At discharge, treatment outcome and referral decisions will be recorded. Six months after discharge, patients will be administered MATE-Outcome, EQ-5D, and CSSRI-EU during a telephone interview. DISCUSSION: This trial will provide evidence on the effects and costs of using placement-matching guidelines based on a standardized assessment with structured feedback in the treatment of alcohol-dependent patients. A process evaluation will be conducted to facilitate better understanding of the relationship between the use of guidelines, outcomes, and potential mediating variables. TRIAL REGISTRATION: German Clinical Trials Register DRKS00005035. Registered 03 June 2013.